2008
DOI: 10.1186/1471-2407-8-62
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant letrozole in postmenopausal estrogen and/or progesterone receptor positive breast cancer: A phase IIb/III trial to investigate optimal duration of preoperative endocrine therapy

Abstract: Background: In recent years, preoperative volume reduction of locally advanced breast cancers, resulting in higher rates of breast-conserving surgery (BCS), has become increasingly important also in postmenopausal women. Clinical interest has come to center on the third-generation nonsteroidal aromatase inhibitors (AIs), including letrozole, for such neoadjuvant endocrine treatment. This usually lasts 3-4 months and has been extended to up to 12 months, but optimal treatment duration has not been fully establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 14 publications
0
55
0
2
Order By: Relevance
“…However, these studies did not determine the optimum duration of treatment. Therefore, Krainick-Strobel et al [25] investigated the optimal duration of neoadjuvant letrozole therapy in postmenopausal patients with HR-positive breast cancer. Their data suggested that prolonged treatment for up to 8 months could result in greater tumor shrinkage compared with treatment for 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not determine the optimum duration of treatment. Therefore, Krainick-Strobel et al [25] investigated the optimal duration of neoadjuvant letrozole therapy in postmenopausal patients with HR-positive breast cancer. Their data suggested that prolonged treatment for up to 8 months could result in greater tumor shrinkage compared with treatment for 4 months.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical tumor responses of neoadjuvant AIs were analyzed in single-arm trials [11][12][13][14][15][16][17][18][19], which are chronologically listed in Table 2. Three to 12 months of neoadjuvant use of AIs revealed that partial response or complete response rates evaluated by palpation were 41-80%, and progressive disease rates were 0-7%.…”
Section: Neoadjuvant Aromatase Inhibitors For Postmenopausal Women Wimentioning
confidence: 99%
“…une phase IIb/III • s'est intéressée à la question de la durée optimale de l'HNA [80], mais ne permet pas d'y répondre. Il s'agit d'une étude conduite, avec le létro-zole, chez 33 femmes seulement, ayant une tumeur RH+, d'emblée non accessible à une CS.…”
Section: Durée De L'hnaunclassified